Pengaruh Kepuasan Kerja Dan Pengembangan Karir Terhadap Kinerja Karyawan Pada PT. Sendok Garpu Internasional Tangerang - Dafa Devika Swari; Derita Qurbani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. This study aims to determine the Effect of Job Satisfaction and Career Development on Employee Performance at PT. Sendok Garpu Internasional Tangerang. The method used is a quantitative method. Data collection techniques using questionnaires. The population in this study were employees of PT. Sendok Garpu Internasional Tangerang. By using the Slovin formula, the research population was 212 employees and the sample used was 68 respondents. Based on the results of the study, the correlation coefficient value or level of influence between the independent variable and the dependent variable was obtained at 0.647, which means the variables have a strong relationship. The coefficient of determination (R Square) value of 0.419 indicates that 41.9% has a simultaneous contribution to the variable, while the remaining 58.1% is influenced by other factors. Hypothesis testing obtained a calculated f value > f table (23.396 > 3.138). With that Ho is rejected and H3 is accepted, it can be concluded that Job Satisfaction and Career Development simultaneously have a positive and significant effect on Employee Performance at PT. Sendok Garpu Internasional Tangerang. Based on the research findings presented in the previous chapters, the analysis and discussion regarding